Journey of Operational Weather Forecasting in India - Sen, P. N.; Chug, Sunny; Bandgar, Arti (MAUSAM, 2025)
India Meteorological Department (IMD) was established in 1875. Its mandate was to study climate and weather of India as a whole and to issue storm and other warnings and daily weather forecast. IMD issues Cyclone Forecasts and Warnings; Day to day Forecasts, Medium Range and Extended Range and Long Range Forecasts; Forecast for Aviation activities; Nowcasting; Quantitative Precipitation Forecast for Flood warning etc. Initially, forecasting was done by Synoptic and Statistical methods. Nowadays, forecasts are issued using Numerical methods. Surface and upper air data along with Radar and Satellite data are used in forecasting work. How the forecasting work evolved in the last one hundred fifty years has been described in this paper.